Rural migration, governance, and public health nexus: Implications for economic development - Yang, Kewen; Fahad, Shah (Frontiers in Public Health, 2022)
With the deepening of rural aging and the increasing role of human capital in the non-agricultural employment labor market, this paper uses the data of China Health and Retirement Longitudinal Study (CHARLS), ordinary least squares (OLS) and instrumental variable method (IV) to try to examine the impact of rural migrant workers' education on their parents' health. Since a rural family may include more than one child, a sample of migrant workers with a high education level is used in the benchmark regression, and a sample of migrant workers with a low education level is used to test the robustness of the relationship. The results showed that the education of migrant workers had a significant positive impact on parents' health. The sample with the least education was used for the robustness，and the results did not change. The IV-probit method is used to address potential endogeneity, and the results remain stable. Heterogeneity analysis shows that there are significant differences in the impact of migrant workers' education on the health of parents from different groups. This positive effect has a greater impact on the health of parents who are older, less educated, and do not live with their children. Mediation analysis shows that children's economic ability, captured by income and work type, and their parents' health behavior, captured by sleep, alcohol consumption, and physical examinations, mediate this relationship. Thus, migrant workers' education affects their parents' health mainly through relaxing budget constraints and improving their parents' health production efficiency. In addition, this paper also found that education of migrant workers may significantly increase parental depression. Based on the above analysis, this paper argues that increasing investment in rural education is conducive to improving the health of migrant farmers' parents, thereby promoting the transfer of rural labor to non-agricultural industries and cities, curbing the rapid rise in labor costs, and promoting the healthy development of the economy.